Missense mutation of VKORC1 leads to medial arterial calcification in rats - Arnaud Michaux (Nature Portfolio, 2018)
Abstract Vitamin K plays a crucial role in the regulation of vascular calcifications by allowing activation of matrix Gla protein. The dietary requirement for vitamin K is low because of an efficient recycling of vitamin K by vitamin K epoxide reductase (VKORC1). However, decreased VKORC1 activity may result in vascular calcification. More than 30 coding mutations of VKORC1 have been described. While these mutations have been suspected of causing anticoagulant resistance, their association with an increase in the risk of vascular calcification has never been considered. We thus investigated functional cardiovascular characteristics in a rat model mutated in VKORC1. This study revealed that limited intake in vitamin K in mutated rat induced massive calcified areas in the media of arteries of lung, aortic arch, kidneys and testis. Development of calcifications could be inhibited by vitamin K supplementation. In calcified areas, inactive Matrix Gla protein expression increased, while corresponding mRNA expression was not modified. Mutation in VKORC1 associated with a limited vitamin K intake is thus a major risk for cardiovascular disease. Our model is the first non-invasive rat model that shows spontaneous medial calcifications and would be useful for studying physiological function of vitamin K.